2021
DOI: 10.1111/jre.12853
|View full text |Cite
|
Sign up to set email alerts
|

TNFα expression by Porphyromonas gingivalis‐stimulated macrophages relies on Sirt1 cleavage

Abstract: Objective Periodontitis is one the most common chronic inflammatory conditions, resulting in destruction of tooth‐supporting tissues and leading to tooth loss. Porphyromonas gingivalis activates host macrophages to secrete pro‐inflammatory cytokines and elicit tissue damage, in part by inducing NF‐kappa‐B transactivation. Since NFκB transactivation is negatively regulated by the Nicotinamide adenine dinucleotide (NAD)‐dependent deacetylase enzyme Sirt1, we sought to assess if RAW264.7 macrophages exposed to P.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 45 publications
0
4
0
Order By: Relevance
“…With their combination, they will regulate the trimethylation of histone H3, lysine 27 (H3K27me3) on promoter regions of genes that define the M2 phenotype, thus promoting M2 macrophage activation ( 25 )( Figure 1 ). In addition, P. gingivalis activates TLR2 and TLR4 and elicits the expression of TNF-α in macrophages ( 26 ). TNF-α is an anti-M2 macrophage factor that blocks M2 macrophage polarization on two levels: through its direct effects on macrophages and the indirect effects of TNF-α on IL-13 production by other innate cell types ( 17 ).…”
Section: Macrophage Polarization In P Gingivalis -...mentioning
confidence: 99%
“…With their combination, they will regulate the trimethylation of histone H3, lysine 27 (H3K27me3) on promoter regions of genes that define the M2 phenotype, thus promoting M2 macrophage activation ( 25 )( Figure 1 ). In addition, P. gingivalis activates TLR2 and TLR4 and elicits the expression of TNF-α in macrophages ( 26 ). TNF-α is an anti-M2 macrophage factor that blocks M2 macrophage polarization on two levels: through its direct effects on macrophages and the indirect effects of TNF-α on IL-13 production by other innate cell types ( 17 ).…”
Section: Macrophage Polarization In P Gingivalis -...mentioning
confidence: 99%
“…Sun et al ( 40 ) found that the dominant bacteria isolated from extraradicular and intraradicular samples from persistent APs were quite different, which suggests that different bacteria play different roles in the pathogenesis of persistent PLs. Considering the fundamental roles of bacteria in the progression of PLs, in this section we summarize the functions of oral bacteria, such as Enterococcus faecalis and P. gingivalis , in the polarization of macrophages ( 41 , 42 ).…”
Section: The Impact Of Bacteria On Macrophage Polarizationmentioning
confidence: 99%
“…Heat-killed P. gingivalis (HKPG) has retained the main virulence factors, like lipopolysaccharide, fimbriae, and peptidoglycan (Akira et al 2006; El-Awady et al 2015). Hence, a frequent stimulus for imitating apical periodontitis in vitro is HKPG, which maintains immunogenicity while preventing culture contamination (Meka et al 2021). Due to an inflammatory response triggered by these pathogenic components, the innate and adaptive immune systems engage in an inflammatory destruction of periapical tissues (Márton and Kiss 2000; Fujii et al 2009).…”
Section: Introductionmentioning
confidence: 99%